(untitled) (Prithvi Academic Journal, 2021)
Integrating technology into language teaching and learning is getting popularity in Nepal. Many educational institutions claim that they are adapting to technology in their curricular activities. This study aims to find out the secondary students’ and teachers’ perspectives on the integration of technology in English language teaching (ELT). As a qualitative research, it employs the semi-structured interview to investigate the participants’ experiences of technology integrated language teaching in English as a Foreign Language (EFL) classroom. The findings of the study reported that technology integrated teaching promotes teachers’ and students’ performances, enriches student-centred teaching strategies, develops learning opportunities and brings pedagogical changes. Technology also supports both teachers and students to be productive in language teaching. Technology integrated language teaching and learning advances coordination, cooperation, and collaboration among teachers and students. Various Information and Communication Technology (ICT) tools support both teachers and students to search and use different online materials relevant to their text. However, insufficient ICT infrastructures, poor bandwidth of internet and limited skill of ICT among teachers and students have become the obstacles to incorporate technology in the Nepali education system. To develop students’ and teachers’ skill of adapting to ICT in their language classroom, the concerned authority needs to provide a minimum ICT infrastructure to achieve the educational goals in Nepal.